Building career resilience. Issue 1 (15th January 2015) - Moffett, Jenny; Matthew, Susan; Fawcett, Anne
Abstract : Vets can face a variety of career setbacks and workplace stressors which can profoundly affect their professional and personal lives. This article considers how vets can learn and implement coping skills that can protect against those stressors and foster resilience.